SVF1 Regulates Cell Survival by Affecting Sphingolipid Metabolism in Saccharomyces cerevisiae - Brace, Jennifer L. (Copyright © 2007 by the Genetics Society of America, 2007)
Sphingolipid signaling plays an important role in the regulation of central cellular processes, including cell growth, survival, and differentiation. Many of the essential pathways responsible for sphingolipid biogenesis, and key cellular responses to changes in sphingolipid balance, are conserved between mammalian and yeast cells. Here we demonstrate a novel function for the survival factor Svf1p in the yeast sphingolipid pathway and provide evidence that Svf1p regulates the generation of a specific subset of phytosphingosine. Genetic analyses suggest that Svf1p acts in concert with Lcb4p and Lcb3p to generate a localized pool of phytosphingosine distinct from phytosphingosine generated by Sur2p. This subset is implicated in cellular responses to stress, as loss of SVF1 is associated with defects in the diauxic shift and the oxidative stress response. A genetic interaction between SVF1 and SUR2 demonstrates that both factors are required for optimal growth and survival, and phenotypic similarities between svf1Δsur2Δ and ypk1Δ suggest that pathways controlled by Svf1p and Sur2p converge on a signaling cascade regulated by Ypk1p. Loss of YPK1 together with disruption of either SVF1 or SUR2 is lethal. Together, these data suggest that compartmentalized generation of distinct intracellular subsets of sphingoid bases may be critical for activation of signaling pathways that control cell growth and survival.